PENGARUH STRUKTUR MODAL, PROFITABILITAS, KEPEMILIKAN MANAJERIAL, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2017 - Wilda Sofia Rini, 15.05.52.0287; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the Effect of Capital Structure, Profitability, Managerial Ownership, and Company Size on the Value of Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2014-2017 Period. The population in this study are all Manufacturing Companies listed on the Stock Exchange for the 2014-2017 Period. The sample selection uses the purpose sampling method. The analytical tool used in this study is multiple linear regression analysis. The test results show that the Capital Structure has a significant positive effect on Firm Value, Profitability has a significant positive effect on Firm Value, Managerial Ownership has a Negative effect that is not significant to the Firm Value, and the Firm Size does not significantly influence the Firm Value.